2018
DOI: 10.1111/ajad.12737
|View full text |Cite
|
Sign up to set email alerts
|

Concomitant drug abuse of opioid dependent patients in maintenance treatment detected with a multi‐target screening of oral fluid

Abstract: Our study underscores the importance of monitoring a broad range of substances including others than usually screened in opioid-dependent patients in OMT. (Am J Addict 2018;XX:1-6).

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
8
0
1

Year Published

2018
2018
2022
2022

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 17 publications
(9 citation statements)
references
References 23 publications
0
8
0
1
Order By: Relevance
“…2,6 Today, OMT is the most common and effective treatment for opioid dependence. 3,[7][8][9][10] To illustrate the effectiveness of OMT, Tran, Ohinmaa, Mills, et al 11 found that the proportion of self-reported opioid use among patients in OMT with continued opioid use decreased from 99.7% from baseline to 14.6% at 9-month follow-up.…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations
“…2,6 Today, OMT is the most common and effective treatment for opioid dependence. 3,[7][8][9][10] To illustrate the effectiveness of OMT, Tran, Ohinmaa, Mills, et al 11 found that the proportion of self-reported opioid use among patients in OMT with continued opioid use decreased from 99.7% from baseline to 14.6% at 9-month follow-up.…”
Section: Introductionmentioning
confidence: 99%
“…Several sources reported misuse of alcohol, benzodiazepines (BZD), amphetamines, cannabis, cocaine, and OMT medications. 7,10,[12][13][14] Synthetical opioids such as methadone, buprenorphine, and fentanyl are increasingly misused. 10 Frequent substance use and polydrug use in OMT is aproblem, 8,9,15 and such use is associated with dropout from OMT.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Diğer maddelere ulaşamama, düşük maliyet, sosyalleşmenin artması, için gabapentinoidlerin daha sık kullanılmasına neden olur(15,16).İsveç'te bir opioid idame tedavisi kliniğinde, hastaların %21'i, en yaygın olarak duygusal sorunları gidermek için (%65) veya eğlence için (%27) ömür boyu tıbbi olmayan pregabalin kullandığını bildirdi(17). Benzer şekilde, opioid idame tedavisi alan hasta örnekleri arasında, İsrailli hastaların %17,7'si aktif reçete olmamasına rağmen pregabalin için pozitif test verirken(18), Almanya'da reçetesiz pregabalin ve gabapentin kullanımı hastaların sırasıyla %18,8 ve %1'inde tanımlandı(19). Bir kullandığını bildirdi.…”
unclassified
“…Concomitant drug abuse is a serious issue, especially among opioid-dependent patients in replacement therapy. 1 Clinical and epidemiological studies show that substance use disorders and psychiatric disorders are highly comorbid, 2 and psychiatric disorders are often accompanied by diverse medications, such as selective serotonin reuptake inhibitors and others. Due to drug interactions, substituted patients who use dextromethorphan are, therefore, exposed to a higher risk of developing (additional) psychiatric symptoms or serotonin syndrome, because high doses of dextromethorphan can result in hallucinations and mania.…”
mentioning
confidence: 99%